Restoring Balance and Symmetry to the Aging Nose - Unadkat, Samit N.; Saleh, Hesham A. (Facial Plastic Surgery, 2021)
Accurate assessment of facial symmetry is a key component of successful rhinoplasty surgery but is often overlooked by both surgeon and patient. Up to three-quarters of patients with a significantly crooked nose have been found to have concurrent marked facial asymmetry. Whilst not a contraindication to rhinoplasty, provided that facial asymmetry is identified in advance and expectations realistic, the correction of nasal deformities can improve perceived facial asymmetry. In the aging face, aside from soft tissue and bony resorption that can amplify facial asymmetry, there are specific surgical challenges to the aging nose; the normal tip support mechanisms deteriorate with age giving rise to distinctive changes to the aging nose—typically tip ptosis and a hanging columella; bone quality becomes more brittle and skin overlying this area becomes thinner. There is also weakening of the external nasal valve thus causing functional impairment too. As a result, rhinoplasty techniques used in younger patients may not be suitable in the aging nose. In this article, the authors describe their experience and outline the evidence on the management of the aging patient with facial and nasal asymmetry.
Keywords: aging; face; nasal septum; surgical procedures; rhinoplasty